2016
DOI: 10.1093/jac/dkw199
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study on breakthrough invasive fungal infections in high-risk patients receiving antifungal prophylaxis

Abstract: Rates of bIFIs observed in our population were comparable to previous data. There was no clear shift towards rare species, as previously reported. A high variety of treatment approaches was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 22 publications
10
29
0
1
Order By: Relevance
“…Another explanation for high IFI incidence may be the unpredictable or sometimes poor bioavailability of antifungal agents (especially posaconazole) used for prophylaxis. In the literature, observational studies on bIFI have reported incidences of probable/proven bIFI ranging from 3% to 13% (22)(23)(24)(25)(26)(27)(28). The rate of bIFI observed in the group receiving prophylaxis is compatible with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…Another explanation for high IFI incidence may be the unpredictable or sometimes poor bioavailability of antifungal agents (especially posaconazole) used for prophylaxis. In the literature, observational studies on bIFI have reported incidences of probable/proven bIFI ranging from 3% to 13% (22)(23)(24)(25)(26)(27)(28). The rate of bIFI observed in the group receiving prophylaxis is compatible with the literature.…”
Section: Discussionsupporting
confidence: 83%
“…Ten patients (21.7%) had mixed IFIs, seven patients (15.2%) had concurrent IFIs and 11 patients had breakthrough IFIs (23.9%). Of these, breakthrough IFI is well‐known risk factor for mortality in remission induction chemotherapy of AML patients and allo‐HSCT recipients . Similarly, multivariate analysis in our study showed that breakthrough IFI is an independent predictor of poor outcome (aHR = 1.99, 95% CI: 1.3‐4.41, P = .031).…”
Section: Discussionsupporting
confidence: 74%
“…These recent advances in the use of PAP during chemotherapy and haematopoietic stem cell transplantation (HSCT) have reduced the number of IFIs and improved the survival of high‐risk patients . However, they have also led to changes in the epidemiology of IFIs, and breakthrough IFIs that developed during treatment with mould‐active azoles have been reported . Thus, concerns on increasing possibility of rare and more resistant mould infections have been raised, and recent reports have described increasing incidence of non‐ Aspergillus invasive mould infections (NAIMIs), often in patients receiving mould‐active azole drugs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At first glance it appears obvious to choose a triazole for first‐line treatment, however, most patients at risk will already receive triazole prophylaxis. A switch in antifungal drug class upon presumed breakthrough aspergillosis is plausible, but has not been subject to randomised clinical trials …”
Section: Introductionmentioning
confidence: 99%